Pustulosis Eksantematosa Akut Umum dengan Disfungsi Organ: Laporan Kasus - Alfadli, Robby; Khairunisa, Salsa (Cermin Dunia Kedokteran, 2025)
Background: Acute generalized exanthematous pustulosis (AGEP) is a severe cutaneous adverse reaction most commonly triggered by medications, particularly antibiotics. AGEP is characterized by the rapid onset of numerous small, sterile, non-follicular pustules on an erythematous base. Case: A 38 year-old female with a rapidly progressing rash, fever, and malaise after taking cefxime for surgical wound. Physical examination revealed difuse, erythematous plaques with numerous small, non-follicular pustules distributed to almost the entire body except the face. Laboratory fndings were leukocytosis and neutrophilia. Patient was treated with dexamethasone and ampicillin sulbactam injections. But skin reactions were severely worsened accompanied by a worsened vital signs, necessitating Intensive Care Unit (ICU) monitoring. The total EuroSCAR score is 9, categorized as defnite AGEP. Skin resolution occurred after 5 days of corticosteroid therapy. Discussion: The use of antibiotics is one of the triggering factors for AGEP. In this case, skin reactions appeared within 24-48 hours after drug exposure. Conclusion: AGEP is a rare clinical condition. Identifying and discontinuing the causative drug is crucial for successful treatment.